2008
DOI: 10.1007/s00415-008-0701-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of subthalamic deep brain stimulation on bradykinesia of proximal and distal upper limb muscles in Parkinson's disease

Abstract: The data suggest that bilateral stimulation of the subthalamic nucleus improves bradykinesia of both distal and proximal muscles of the arm and hand in Parkinson's disease; however, dependent upon task complexity proximal and distal movement components may be affected differentially. Kinematic motion analysis is an efficient tool to objectively evaluate the beneficial effects of subthalamic nucleus stimulation on dexterity in Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
3
18
1
1
Order By: Relevance
“…In another study, STN-HFS had an impact on simple alternating distal (index finger tapping) and proximal movements (pointing), when tested in isolation. However, there was a differential impact of STN-HFS on finger bradykinesia within a complex reach-to-grasp task where both components were combined [1]. Our data corroborate these findings by demonstrating significant improvements in distal and proximal tapping with STN-HFS compared with the off state, but a greater impact on the proximal tapping task compared with the distal tapping.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In another study, STN-HFS had an impact on simple alternating distal (index finger tapping) and proximal movements (pointing), when tested in isolation. However, there was a differential impact of STN-HFS on finger bradykinesia within a complex reach-to-grasp task where both components were combined [1]. Our data corroborate these findings by demonstrating significant improvements in distal and proximal tapping with STN-HFS compared with the off state, but a greater impact on the proximal tapping task compared with the distal tapping.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, there has been an interest in distinguishing proximal from distal arm bradykinesia in PD [1, 2, 4], as they are thought to originate within different neuronal networks and seem to respond differently to treatment. The aim of this study was to evaluate a simple tapping device, which measures the speed of repetitive alternating proximal and distal arm movements in PD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the medication and DBS may modify the tremor amplitude, regularity and frequency [4,41,42], movement speed [3,8,34,40,44,49,51,52], joint kinetics and muscle activation during movements [55], EMG burst patterns during movement [34,51,52] and the cortico-muscular coherence [25,37]. There is currently a lot of interest for characterizing EMG and kinematic signals of PD patients.…”
Section: Surface Electromyography and Kinematic Measurements In Pdmentioning
confidence: 99%